DOI: 10.25148/etd.fi10022502
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Lotka’s law in the Field of Library and Information Studies

Abstract: We have read this dissertation and recommend that it be approved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 47 publications
0
17
0
2
Order By: Relevance
“…In Lotka's seminal paper {Lotka:1926vc}, he found that "the number ( (29). In the field of CCM, the n and c value differed significantly from the Lotka's law, which may not be suitable for the measurement of authors' productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lotka's seminal paper {Lotka:1926vc}, he found that "the number ( (29). In the field of CCM, the n and c value differed significantly from the Lotka's law, which may not be suitable for the measurement of authors' productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2,000 highly cited articles, Bellomo R contributed the most [30], followed by Vincent JL [29], Bernard GR [21], Angus DC [17], and Reinhart K [17] (Figure 2). The United State of America contributed more than half (50.7%) of the highly cited articles, followed by Canada (8.4%), France (7.2%), Germany (4.3%), Australia (3.4%), Spain (3.2%), Italy (3.0%), Netherlands (2.4%), Belgium (2.2%), Switzerland (1.8%), Sweden (1.4%) and China (1.0%), as shown in Figure 3.…”
Section: Leading Contributors Of the Highly Cited Articlesmentioning
confidence: 99%
“…In relation to the research base of a profession, examination of author productivity has been used as proxy to demonstrate scholarly maturity . Diagnostic radiography author productivity has only been reviewed on one longitudinal single‐journal study, but studies from other disciplines have concluded that the most productive authors will contribute disproportionately to the evidence base and is illustrated by Baker et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kajian-kajian selanjutnya yang dilakukan o l e h p a r a p e n e l i t i b e r k a i t a n d e n g a n produktivitas penulis dalam berbagai bidang ilmu pengetahuan, menunjukkan hasil yang sesuai dengan dalil tersebut (Askew, 2008;Lin, 2011;Anwar, 2012;Wahyudi, 2015). Meskipun demikian, ada juga hasil kajian yang tidak sesuai dengan dalil tersebut.…”
Section: B Tinjauan Pustaka Bibliometriunclassified
“…Adanya perbedaan yang signifikan antara hasil pengamatan dan teori diprediksikan karena penghitungan dengan melibatkan seluruh penulis, sementara kajian yang dilakukan Lotka hanya terbatas pada penulis pertama (Askew, 2008).…”
Section: B Keterlibatan Penulis Secara Keseluruhanunclassified